2021
DOI: 10.5423/ppj.oa.11.2020.0208
|View full text |Cite|
|
Sign up to set email alerts
|

Carbamoyl Phosphate Synthase Subunit CgCPS1 Is Necessary for Virulence and to Regulate Stress Tolerance in Colletotrichum gloeosporioides

Abstract: Glomerella leaf spot (GLS) is a severe infectious disease of apple whose infective area is growing gradually and thus poses a huge economic threat to the world. Different species of Colletotrichum including Colletotrichum gloeosporioides are responsible for GLS. For efficient GLS control, it is important to understand the mechanism by which the cruciferous crops and C. gloeosporioides interact. Arginine is among one of the several types of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…We found that, compared to the wild-type, the appressorium formation rate and pathogenicity of the mutant ∆Cglac13H significantly decreased, which was consistent with the results of LAC1 and Cglac10 [36,52]. In addition, the knockout of the CgHOS2 [53], CgHSF1 [8], CgGa1 [54], CgCPS1 [55], CgOPT2 [56], and CgEnd3 [57] genes in C. gloeosporioides had the same results. This illustrates that Cglac13 significantly affected the appressorium formation and pathogenicity in C. gloeosporioides.…”
Section: Discussionsupporting
confidence: 86%
“…We found that, compared to the wild-type, the appressorium formation rate and pathogenicity of the mutant ∆Cglac13H significantly decreased, which was consistent with the results of LAC1 and Cglac10 [36,52]. In addition, the knockout of the CgHOS2 [53], CgHSF1 [8], CgGa1 [54], CgCPS1 [55], CgOPT2 [56], and CgEnd3 [57] genes in C. gloeosporioides had the same results. This illustrates that Cglac13 significantly affected the appressorium formation and pathogenicity in C. gloeosporioides.…”
Section: Discussionsupporting
confidence: 86%
“…Certainly, the deletion of CgloRPCYG led to lower pathogenicity in apple, pear, and mango fruits in this study, indicating that CgloRPCYG functions as a pathogenicity factor. In C. gloeosporioides, knockout of the CgHOS2 [52], CgHSF1 [53], CgGa1 [54], CgCPS1 [55], CgOPT2 [56], and CgEnd3 [57] genes showed the same result. C. gloeosporioides produce conidia, exhibit conidial germination and appressorium, form penetration pegs, and invade hosts, thus causing plant disease.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, two gene-encoding arginase and argininosuccinate synthase in mutants were fully blocked. The deletion of carbamoyl-phosphate synthase in Colletotrichum gloeosporioides led to a slow growth rate and an extreme sensitivity to high osmotic stress [39]. Up-regulation of arginase could alleviate damage to plants caused by salinity [40].…”
Section: Discussionmentioning
confidence: 99%